Middle Eastern Culture Representation In Prince Ali’s Music Video In The Film Aladdin - Utomo, Ardian; Widhihatmini; Utari, Tituk; Asgawanti , Eka Desy; Oktaviani, Dhian (Universitas Lancang Kuning, 2025)
Music video clips are one of the communication media that can influence their audience. In addition, music video clips are also an alternative entertainment for listeners and viewers. The Walt Disney Company is a film producer that has produced many musical films and has many fans worldwide. In this study, we will analyze the music video clip of the song titled Prince Ali from the film Aladdin, where this film is one of Disney's production films that was remade from the previous version; in addition, this video clip shows a potent blend of western and middle eastern culture using. This research approach uses Roland Barthes' semiotics to see the Middle Eastern culture represented in this music video clip. As is known, many people still believe that the Middle East is identical to deserts and high temperatures, but the illustrations depicted in this video clip are not as perceived. This study uses a constructivist paradigm with a qualitative descriptive interpretative approach, where researchers interpret data to obtain deep and broad meaning and significance to the research results. In the denotative and connotative meanings, the depiction of the Middle East in the music video clip of Prince Ali in the film Aladdin shows the crowd in the Middle of the market passed by Prince Ali's entourage who came with luxury and splendor to propose to Princess Jasmine. The myth that can be analyzed in this study is that in the Middle East, not all women wear the veil and dress all in black, and luxury and wealth cannot always conquer a woman's heart, but honesty and simplicity. The results of the study show how the representation of Middle Eastern culture in the video clip in the film Aladdin through denotative, connotative, and myth analysis reveals a deeper dimension of stereotypes, social views, and more universal values, which ultimately show that women in the Middle East are not only defined by their appearance and that honesty and simplicity have the power to change human views and relationships